Cost Analysis of a Composite Diagrid Structure Frame with Bare Frame under Dynamic Loading - Soni, Satyendra Kumar; Sathbhaiya, Rahul (International Journal of Scientific Research in Civil Engineering, 2020)
As now days a huge requirement of tall structure is needed due to increasing population in India, As India is a developing country which has moderate economy therefore cost of project plays a vital role in acceptance of technology and its application. In this paper, the author has compared the cost of construction of a high-rise building with and without diagrids. Authors have analyses a G+11 storey building in different seismic zones with different types of soil using software Staad.pro V8i. Total eight cases were modelled and designed for comparison. At the end concluded that introduction of Steel diagrid members decreases the cost of same building. It was found that diagrid structure is also capable of reducing the effect of dynamic loading on building.